EXPERIENCE OF ENDOSCOPIC CORRECTION OF CONGENITAL DIAPHRAGMATOCELE IN NEWBORNS - A. Y. Tarasov; V. A. Savvina; A. R. Varfolomeev; V. N. Nikolaev (Union of pediatricians of Russia, 2013)
Study aim: analysis of surgical treatment of congenital diaphragmatocele on the basis of еру multi-profile republican hospital #1 of the National center of medicine. Study participants and methods. The article gives analysis of treatment results for 8 newborns (6 girls and 2 boys) with false diaphragmatoceles. The average age at the moment of operation was 3 days. In 6 cases the malformation was revealed antenatally during ultrasound investigation within a prescribed period, in 3 cases - within the first antenatal hours. Results. All patients were operated thoratoscopically, average operation time - 60 minutes. No intraoperative complications, hemorrhage or conversion. Average time of post-operative artificial pulmonary ventilation - 5.6 days, of pleural draining - 4.7 days. Results were being evaluated from 6 months to 2 years after operation. An excellent direct and long-term functional and cosmetic result was achieved with all patients. Conclusions. Thoracoscopic plastic surgery of defects at false congenital diaphragmatocele introduced in clinical practice is a sufficiently safe procedure for newborns. Excellent visualization of all stages of intervention, lack of technical difficulties with bringing organs down and plastic surgery of the diaphragm itself and quick recovery in the nearest post-operative period are indubitable advantages of endosurgical intervention.